2019
DOI: 10.1111/jomf.12593
|View full text |Cite
|
Sign up to set email alerts
|

Daily Food Insufficiency and Worry among Economically Disadvantaged Families with Young Children

Abstract: Objective: To examine how reports of food insecurity vary daily among low-income parents of young children.Background: The material and emotional components of food insecurity have negative consequences for children and can have negative implications for family life. Though the overall influence of food insecurity on parents and children is well-established, little is understood about possible instability in food insecurity. This paper examines to what degree instability related to the SNAP benefit cycle influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Additionally, studies have demonstrated that even SNAP benefits are not always sufficient to address food insecurity among economically disadvantaged individuals. Furthermore, food insecurity status varies on a daily basis within the month where SNAP benefits are received (Gassman-Pines & Schenck-Fontaine, 2019). This variation is an additional contributor to allostatic load, which is related to poor health outcomes and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have demonstrated that even SNAP benefits are not always sufficient to address food insecurity among economically disadvantaged individuals. Furthermore, food insecurity status varies on a daily basis within the month where SNAP benefits are received (Gassman-Pines & Schenck-Fontaine, 2019). This variation is an additional contributor to allostatic load, which is related to poor health outcomes and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐income students who eat breakfast at school have improved overall diet quality compared to those who skip breakfast or eat it elsewhere 26 . In addition, consuming a well‐balanced diet earlier in life lays the foundation for healthy eating habits that typically continue into adulthood 3 …”
Section: Discussionmentioning
confidence: 99%
“…The evidence for the United States indicates that food insecurity is disproportionately high in African American and Hispanic households with incomes below the official poverty line 2 . Food insecurity is defined by limited and uncertain access to nutritional food products and the associated psychological anxieties about food availability and sufficiency 3 …”
mentioning
confidence: 99%
“…These measures are self‐reported, not clinical, measures of well‐being. The measures, or very similar measures, have been used and validated in prior studies (Almeida, 2005; Gassman‐Pines & Schenck‐Fontaine, 2019). The sleep quality measures were reverse coded so that higher numbers indicated worse perceived sleep quality.…”
Section: Methodsmentioning
confidence: 99%